EXTH-10. COMBINATION OF EPIGENETIC ENZYME INHIBITORS, GSK-J4 AND BELINOSTAT, REVEALS HIGH EFFICACY IN IDH1 MUTANT GLIOMAS. (9th November 2020) - Kayabolen, Alisan; Sahin, Gizem Nur; Seker, Fidan; Cingoz, Ahmet; Isik, Bekir; Acar, Simge; Wakimoto, Hiroaki; Cahill, Daniel; Solaroglu, Ihsan; Cribbs, Adam; Oppermann, Udo; Bagci-Onder, Tugba
Abstract: Mutations in IDH1 and IDH2 genes are common in low grade gliomas and secondary GBM and are known to cause a distinct epigenetic landscape in these tumors. To interrogate the epigenetic vulnerabilities of IDH -mutant gliomas, we performed a chemical screen with inhibitors of chromatin modifiers and identified 5-azacytidine, Chaetocin, GSK-J4 and Belinostat as potent agents against primary IDH1 -mutant cell lines. Testing the combinatorial efficacy of these agents, we demonstrated GSK-J4 and Belinostat combination as a very effective treatment for the IDH1 -mutant glioma cells. Engineering established cell lines to ectopically express IDH1 R132H, we showed that I DH1 R132H cells adopted a different transcriptome with changes in stress-related pathways that were reversible with the mutant IDH1 inhibitor, GSK864. The combination of GSK-J4 and Belinostat was highly effective on IDH1 R132H cells, but not on wt glioma cells or nonmalignant fibroblasts and astrocytes. The cell death induced by GSK-J4 and Belinostat combination involved the induction of cell cycle arrest and apoptosis. RNA sequencing analyses revealed activation of inflammatory and unfolded protein response pathways in IDH1 -mutant cells upon treatment with GSK-J4 and Belinostat conferring increased stress to glioma cells. Specifically, GSK-J4 induced ATF4-mediated integrated stress response and Belinostat induced cell cycle arrest in primary IDH1 -mutant glioma cells; which were accompanied by DDIT3 /CHOP-dependent upregulation of apoptosis. Moreover, to dissect out the responsible target histone demethylase, we undertook genetic approach and demonstrated that CRISPR/Cas9 mediated ablation of both KDM6A and KDM6B genes phenocopied the effects of GSK-J4 in IDH1 -mutant cells. Finally, GSK-J4 and Belinostat combination significantly decreased tumor growth and increased survival in an orthotopic model in mice. Together, these results suggest a potential combination epigenetic therapy against IDH1 -mutant gliomas.